A conceptual model for ethical business decision making under the influence of personal relationships. (26th August 2008) - Davidrajuh, Reggie
This paper proposes a conceptual model for ethical business decision making. The purpose of this model is to explore the ethical implications of personal relationship in business exchanges. Firstly, this paper introduces personal relationship in business exchanges. Secondly, three normative theories of ethics that are relevant to the business environment are presented. Thirdly, a literature study on the existing models and frameworks for ethical business decision making is presented. Finally, a new model is presented; this model is developed using an approach based on the Theory of Connection (TOC). The new model supports inclusion of mathematical modules for autonomous ethical business decision making.